Bildende Künstler im Fotoporträt Freundschaft zwischen Porträtfotografen und Künstlermodellen? - Jendrus, Verena (KIT Scientific Publishing, 2022)
To define the social interactions of a photographer and the portrayed artist as friendship is a recurring topos in art. However, only in some instances can the photographic portrait fulfill the concrete visibility represented in romantic paintings. Do the attributes of portraiture of a friend remain as unspecified as the hope for authenticity and intimacy ascribed to the term friendship?